Discursive Strategies of Speeches of The World Health Organization Director-General on Handling Covid-19 - Muhassin, Mohammad; Hidayati, Dewi Ayu (English Education: Jurnal Tadris Bahasa Inggris, 2023)
Speeches have been analyzed from multiple perspectives, yet the literature reveals gaps in the examination of discursive strategies and speech functions. To address this issue, this study aims to uncover the discursive strategies and speech functions utilized by Dr. Tedros, Director-General of the World Health Organization (WHO), in his speeches on managing Covid-19. This qualitative content analysis employs purposive sampling of speeches from YouTube, specifically speeches given at the onset and conclusion of the pandemic.The findings indicate that Dr.Tedrosemployede motive,imperative,metaphorical,hyperbolic,and personification language to convey his message.Furthermore,only three speech functions were identified: statements, commands, and offers. This underscores Dr. Tedros's focus on delivering precise and persuasive information regarding Covid-19 management. This study offers implications for future research and discourse analysis